COMPARATIVE POPULATION GENOMICS IN COLLINSIA SISTER SPECIES REVEALS EVIDENCE FOR REDUCED EFFECTIVE POPULATION SIZE, RELAXED SELECTION, AND EVOLUTION OF BIASED GENE CONVERSION WITH AN ONGOING MATING SYSTEM SHIFT. (11th January 2013) - Hazzouri, Khaled M.; Escobar, Juan S.; Ness, Rob W.; Killian Newman, L.; Randle, April M.; Kalisz, Susan; Wright, Stephen I.
Abstract : Selfing species experience reduced effective recombination rates and effective population size, which can lead to reductions in polymorphism and the efficacy of natural selection. Here, we use illumina transcriptome sequencing and population resequencing to test for changes in polymorphism, base composition, and selection in the selfing angiosperm Collinsia rattanii (Plantaginaceae) compared with its more outcrossing sister species Collinsia linearis . Coalescent analysis indicates intermediate species divergence (500, 000–1 million years) with no ongoing gene flow, but also evidence that the C. rattanii clade remains polymorphic for floral morphology and mating system, suggesting either an ongoing shift to selfing or a potential reversal from selfing to outcrossing. We identify a significant reduction in polymorphism in C. rattanii, particularly within populations. Analysis of polymorphisms suggests an elevated ratio of unique nonsynonymous to synonymous polymorphism in C. rattanii, consistent with relaxed selection in selfing lineages. We additionally find higher linkage disequilibrium and differentiation, lower GC content at variable sites, and reduced expression of genes important in pollen production and pollinator attraction in C. rattanii compared with C. linearis . Together, our results highlight the potential for rapid shifts in the efficacy of selection, gene expression and base composition associated with ongoing evolution of selfing.